2019
DOI: 10.1038/s41598-019-45078-2
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast modulation of cardiac myocyte structure and function

Abstract: After myocardial infarction, resident fibroblasts (Fb) differentiate towards myofibroblasts (MyoFb), generating the scar tissue and the interstitial fibrosis seen in the adjacent myocardium. Fb and MyoFb have the potential to interact with cardiac myocytes (CMs) but insight into the phenotype-specific role and mode of interaction is still incomplete. Our objectives are to further define the modulation of CMs by MyoFbs compared to Fbs, as well as the role of direct contact through gap junctions vs. soluble medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 35 publications
3
38
0
Order By: Relevance
“…The absence of CaT alteration in the MSC co-cultures reinforces the hypothesis that cardiac fibroblasts specifically influence cardiomyocytes to specialize into fast-conducting fibers. Other studies have reported similar functional changes related to excitation–contraction coupling when cardiomyocytes are under the influence of cardiac fibroblasts 32 , 45 48 . Recently, Nagaraju et al showed that myofibroblasts coupled with cardiomyocytes can also modulate cardiomyocyte action potentials 48 .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The absence of CaT alteration in the MSC co-cultures reinforces the hypothesis that cardiac fibroblasts specifically influence cardiomyocytes to specialize into fast-conducting fibers. Other studies have reported similar functional changes related to excitation–contraction coupling when cardiomyocytes are under the influence of cardiac fibroblasts 32 , 45 48 . Recently, Nagaraju et al showed that myofibroblasts coupled with cardiomyocytes can also modulate cardiomyocyte action potentials 48 .…”
Section: Discussionsupporting
confidence: 59%
“…Other studies have reported similar functional changes related to excitation–contraction coupling when cardiomyocytes are under the influence of cardiac fibroblasts 32 , 45 48 . Recently, Nagaraju et al showed that myofibroblasts coupled with cardiomyocytes can also modulate cardiomyocyte action potentials 48 . Similarly, they observed hyperpolarization of the resting membrane potential; however, action potential duration was faster in cardiomyocytes coupled with myofibroblasts.…”
Section: Discussionsupporting
confidence: 59%
“…Even though mRNAs for some markers of fibrosis and extracellular matrix were more abundant in some cell lines (AT1, NCR, REB), increased fibrosis could not be confirmed histologically and was absent in all investigated slides with the exception of a few collagen fibrils on the surface of ERC-EHT. However, this issue should be taken into consideration when working with multicellular EHT preparations or different matrix protein such as collagen in the future ( Giacomelli et al., 2020 ; Li et al., 2017 ; Mills et al., 2017 ; Nagaraju et al., 2019 ). (7) Predominance of cells with atrial or ventricular-like phenotype could theoretically explain differences in baseline contractility.…”
Section: Discussionmentioning
confidence: 99%
“…Increased compaction and stiffness were expected, as cardiac fibroblasts are a remodeling and ECM-producing cell type; however, the increased MCR was surprising, given the previous reports that cardiac fibroblasts are nonexcitable cells which decrease beating rate with increasing percentage [ 58 ]. A possible explanation is that the higher fibroblast content may have caused cardiac myocyte electromechanical remodeling including shortening of APDs and hyperpolarizing resting membrane potentials [ 59 ], resulting in increased MCR and spontaneous activity of ECTs with 10% and 15% hCFs. Further evidence for this was demonstrated through optical mapping of ectopic activity in 15% hCF ECTs.…”
Section: Discussionmentioning
confidence: 99%